PROSEDUR KEARIFAN LOKAL MASYARAKAT ETNIS BETAWI RELASINYA DENGAN OTONOMI DAERAH KHUSUS DKI JAKARTA - B.S, Dwi Andayani; Fadhlillah, Muhammad Rizqi; Rusmadi, Eno (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
Jakarta's current government administration is based on certain specificities or is equated with other regional governments. As the capital of the Republic of Indonesia, the city of Jakarta is experiencing very rapid growth. DKI Jakarta is given the privilege of being a special region which is formally regulated in Law Number 29 of 2007. Article 26 paragraph 6 of Law Number 29 of 2007 states that the Provincial Government of DKI Jakarta to preserve and develop the culture of the Betawi people and protect the various cultures of other regional communities in the DKI Jakarta Province, including local wisdom from the Betawi people who are part of DKI Jakarta. The research method used is normative juridical research. In its implementation, it turns out that local wisdom is not significantly felt in the DKI Jakarta area. The completion of the development of the Archipelago Capital City in Kalimantan could change the specificities that the DKI Jakarta Province has in the Law, so it is hoped that there will be changes in DKI Jakarta in the policy of implementing the local wisdom of the Betawi ethnic community in the City of Jakarta. Keywords: Local Wisdom, Law, Government